Management Strategy for marine turtle conservation on the Caribbean Coast of Nicaragua / Cynthia J. Lagueux y otros - Lagueux, Cynthia J. Cambell, Cathi L. (Nicaragua: Wildlife conservation society, 2005)
It is increasingly recognized that maintaining biodiversity is of fundamental importance toward sustaining human livelihoods. One of the major assets of the region identified as.
1. Caribbean Nicaragua - Historical Harvest 2. Ecological Role
Incluye Indice
Col. Agro
Keywords: 1. HISTORICAL USE, CURRENT THREATS, AND VALUE OF SEA TURTLES 2. LEGAL PROTECTION FOR SEA TURTLES